Information retrieval technology : Second Asia Information Retrieval Symposium, AIRS 2005, Jeju Island, Korea, October 13-15, 2005 : proceedings - Asia Information Retrieval Symposium ( 2nd : 2005: Cheju-do, Korea); Lee, Gary Geunbae, 1961- (Berlin : Springer, 2005)
99